Autoimmune Diseases in Patients With Myotonic Dystrophy Type 2 - Stojan Peric; Stojan Peric; Jelena Zlatar; Luka Nikolic; Vukan Ivanovic; Jovan Pesovic; Ivana Petrovic Djordjevic; Ivana Petrovic Djordjevic; Svetlana Sreckovic; Svetlana Sreckovic; Dusanka Savic-Pavicevic; Giovanni Meola; et al. (Frontiers in Neurology, 2022)
IntroductionMyotonic dystrophy type 2 (DM2) is a rare autosomal dominant multisystemic disease with highly variable clinical presentation. Several case reports and one cohort study suggested a significant association between DM2 and autoimmune diseases (AIDs).AimThe aim of this study is to analyze the frequency and type of AIDs in patients with DM2 from the Serbian DM registry.Patients and MethodsA total of 131 patients with DM2 from 108 families were included, [62.6% women, mean age at DM2 onset 40.4 (with standard deviation 13) years, age at entering the registry 52 (12.8) years, and age at analysis 58.4 (12.8) years]. Data were obtained from Akhenaten, the Serbian registry for DM, and through the hospital electronic data system.ResultsUpon entering the registry, 35 (26.7%) of the 131 patients with DM2 had AIDs including Hashimoto thyroiditis (18.1%), rheumatoid arthritis, diabetes mellitus type 1, systemic lupus, Sjogren's disease, localized scleroderma, psoriasis, celiac disease, Graves's disease, neuromyelitis optica, myasthenia gravis, and Guillain-Barre syndrome. At the time of data analysis, one additional patient developed new AIDs, so eventually, 36 (28.8%) of 125 DM2 survivors had AIDs. Antinuclear antibodies (ANAs) were found in 14 (10.7%) of 63 tested patients, including 12 without defined corresponding AID (all in low titers, 1:40 to 1:160). Antineutrophil cytoplasmic antibodies (ANCAs) were negative in all 50 tested cases. The percentage of women was significantly higher among patients with AIDs (82.9% vs. 55.2%, p <0.01).ConclusionAIDs were present in as high as 30% of the patients with DM2. Thus, screening for AIDs in DM2 seems reasonable. Presence of AIDs and/or ANAs may lead to under-diagnosis of DM2.